Synthesis and Evaluation of 2′-Deoxy-2′-Spirodiflurocyclopropyl Nucleoside Analogs. (1st September 2016) - Liu, Xiao; Xia, Xueliang; Sun, Chenghai; Lin, Cai; Zhou, Yiqian; Hussain, Muzammal; Tang, Fei; Liu, Lu; Li, Xue; Zhang, Jiancun
ABSTRACT: The preparation of 2′-deoxy-2′-siprodifluorocyclopropany-lnucleoside analogs has been achieved from α-d -glucose in several steps. The key step in the synthesis was the introduction of the difluorocyclopropane through a difluorocarbene type reaction at the 2′-position. Then, a series of novel 2′-deoxy-2′-spirodifluorocyclopropanyl nucleoside analogs were synthesized using the Vorbrüggen method. All the synthesized nucleosides were characterized and subsequently evaluated against hepatitis C and influenza A virus strains in vitro .